Foreign Direct Investment, Demand and Econo mic Growth in the Power and Energy Sectors - Kumat Das, Sujit (International Journal of Psychosocial Rehabilitation, 2025)
India makes a major contribution to the overall economy of South Asia, but is faced with a major energy crisis for many years. In the earlier scenario, it has been seen that the economic growth was strong and energy demand was rapidly rising, there were no concerted attempts to meet the country’s energy demand. Like other developing countries, Foreign Direct Investment (FDI) plays a key role in this country’s economic growth. In various sectors of the economy, India has been received FDI from many countries. This paper highlights the current status of the power and electricity industry in India (PESI), and presents an empirical study on FDI causation in the electricity and energy sector, energy consumption and Indian economic growth between 1990 and 2019. In the last few years the FDI market has drawn a relatively higher rate of FDIs over India than the other economic sectors, as shown by the FDI channel. In contrast, energy production levels and the use of resources in previous years show a significant difference. The result showed that economic growth and energy consumption have a strong, two-way, short-term causal relationship. The results also demonstrate the long-term causality in the energy consumption equation. Taking into account the current PESP situation, policymakers ought to draw up strategies to reach the minimum level of debt and to discourage investment dependent on the loans. Such policies would help to control and increase the economic growth of the severe energy crisis. This paper attempts to establish the possible causalities and comparative connections between electricity consumption, foreign direct investment and Indian economic growth.